Assessment of Pozzolanicity of Clay Bricks Fired at Different Temperatures for Use in Repair Mortar - Ulukaya, Serhan; Yuzer, Nabi (ASCE-AMER SOC CIVIL ENGINEERS, 2016)
Crushed bricks used in air lime mortars must show pozzolanic activity to obtain hydraulic products, and peak firing temperature is one of the main parameters for pozzolanicity of the fired clay bricks apart from clay type. In this study, solid clay mortars containing impurities as found in nature, which are used in the production of commercially sold bricks, were pulverized for a uniform firing process and then fired at nine different temperatures. The pozzolanic activity of the fired, pulverized clay was examined by commonly used direct and indirect test methods, and the results were discussed. Phase transformations of the clay and the reactions corresponding to temperature changes were also examined by X-ray diffraction (XRD) and thermogravimetric (TG) analyses. The common result of the methods reveals that clay treated at 850 degrees C can be regarded as the best pozzolan, and the pozzolanicity of clay bricks significantly changes the mechanical properties of crushed brick-lime mortars.
Keywords: Clay; Crushed brick-lime mortars; Firing temperature; Mechanical properties; Pozzolan; Pozzolanic activity tests; CONDUCTIVITY MEASUREMENT; PRODUCTS; ASH; Construction & Building Technology; Engineering; Materials Science